2020
DOI: 10.48550/arxiv.2005.05412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mbsolve: An open-source solver tool for the Maxwell-Bloch equations

Michael Riesch,
Christian Jirauschek

Abstract: The Maxwell-Bloch equations are a valuable tool to model light-matter interaction, where the application examples range from the description of pulse propagation in two-level media to the elaborate simulation of optoelectronic devices, such as the quantum cascade laser (QCL). In this work, we present mbsolve, an open-source solver tool for the Maxwell-Bloch equations. Here, we consider the one-dimensional Maxwell's equations, which are coupled to the Lindblad equation. The resulting generalized Maxwell-Bloch e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Yee's scheme was extended to the light-matter interactions with ultrashort pulse in anisotropic media for the unidimensional case in [36], and bidimensional case in [37], where a pesudo-spectral time-domain method was also discussed, along with similar splitting schemes for Bloch equations. In [38], a Maxwell-Bloch solver for two-level atomic systems was developed. A scrutiny of FDTD numerical methods based on Yee's scheme for nonlinear active materials revealed that they have limitations and restrictions to low-order accuracy, low dimensions, or only two-level atomic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Yee's scheme was extended to the light-matter interactions with ultrashort pulse in anisotropic media for the unidimensional case in [36], and bidimensional case in [37], where a pesudo-spectral time-domain method was also discussed, along with similar splitting schemes for Bloch equations. In [38], a Maxwell-Bloch solver for two-level atomic systems was developed. A scrutiny of FDTD numerical methods based on Yee's scheme for nonlinear active materials revealed that they have limitations and restrictions to low-order accuracy, low dimensions, or only two-level atomic systems.…”
Section: Introductionmentioning
confidence: 99%